Catskill eagle - Parker, Robert B. (Delacorte Press, 1985)
Spenser and Hawk, in an uneasy undercover alliance with federal law enforcement agents, search for Susan Silverman, who is somehow involved with the son of a man the government wants dead
55218
Keywords: Spenser -- (Fictitious character); Private Investigators -- Fiction; Boston, Mass